Diagnostic performance of biomarkers in maternal sepsis: A prospective observational study. Issue 2 (11th February 2021) - Katoch, Tanvi; Singh, Anju; Suri, Vanita; Sethi, Sunil; Sachdeva, Naresh; Naseem, Shano
Abstract: Objectives: Maternal sepsis is a life‐threatening condition. Biomarkers have been found to be useful in early detection of sepsis in the critical care setting. We aimed to determine the diagnostic performance of different biomarkers such as procalcitonin, C‐reactive protein (CRP), absolute eosinophil count, and activated partial thromboplastin time (aPTT) in maternal sepsis. Methods: A total of 35 patients were enrolled in this prospective observational study. Patients with suspected sepsis were evaluated for multi‐organ dysfunction. The blood samples for testing of these biomarker levels were obtained at the time of enrollment in the study (day 1), and on day 3 and day 7. Trends of each marker were followed and correlated with the clinical picture. Results: Of 35 enrolled patients, 30 completed the study. Among these, 18 had sepsis and 12 were designated as without sepsis. Sensitivities of procalcitonin, CRP, aPTT, and absolute eosinophil count were 83.33%, 77.78%, 55.56%, and 58.82% whereas their specificities were 66.67%, 75.0%, 100%, and 75%, respectively. Area under the curve was highest for procalcitonin (0.813) followed in decreasing order by CRP (0.778), aPTT (0.731), and eosinophil count (0.642), respectively. Conclusion: Procalcitonin and CRP may be used as a valuable adjunct in the clinical stepwise approach for the prompt diagnosis of maternal sepsis. Synopsis: Procalcitonin and C‐reactive protein may be used as valuable adjuncts in the clinical stepwise approach for the prompt diagnosis of maternal sepsis.